Reliability and Validity of the Indian (Telugu) Version of the Shoulder Pain and Disability Index - Yatheendra Kumar Gadam; Sudhakar Subramanian; Apparao Patchava; Siva C Kumar; Siva Jyothi Neerukonda; Neethu Kambarthi (Journal of Clinical and Diagnostic Research, 2018)
Introduction: The Shoulder Pain and Disability Index (SPADI) is one of the most commonly used shoulder specific self report questionnaires that is available to evaluate patients with shoulder pathology but it has not been adapted in Telugu version. Aim: The aim of the present study was to translate, culturally adapt, and validate the Telugu version of the SPADI. Materials and Methods: Based on the cross cultural adaptation guidelines stated by the American Association of Orthopaedic Surgeons (AAOS) outcome committee, cross cultural adaptation and psychometric testing of SPADI was conducted at the Outpatient Physiotherapy Department of the Susruta Institute of Physical Medicine and Rehabilitation, Hyderabad, India. The testretest reliability was quantified using the Intraclass Correlation Coefficient (ICC) and Cronbach’s alpha was calculated to assess internal consistency of the Telugu questionnaire. Results: The reliability of the total Telugu SPADI and its subsets (Intraclass correlation coefficient >0.96) were found to be higher than that of the English SPADI and the German SPADI in this population. Conclusion: The cross culturally adapted version of the English SPADI into a regional Indian language (Telugu) is easy to use and is a reliable and valid tool for measuring shoulder pain and disability in the Telugu speaking population.